2010
DOI: 10.1111/j.1751-0813.2010.00629.x
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography diagnosis of eight dogs with brain infarction

Abstract: CT is useful in the diagnosis of cerebrovascular accident in dogs, which can present as a spectrum of images with early changes in attenuation and subtle mass effects detected after infarction. CT is particularly sensitive for detecting haemorrhagic infarction, but under-represent ischaemic and lacunar infarctions when compared with MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 25 publications
2
16
1
Order By: Relevance
“…Of these dogs, 2 had no underlying disease identified, while the 3 others had PLN, HAC, or hemangiosarcoma identified (LOE 5, Fair) . In another study of 8 dogs with brain infarction identified via CT, 6 of 8 dogs had concurrent diseases including hypothyroidism, chronic renal disease, pyometra, and HAC (LOE 5, Fair) . A third study of 22 dogs included 4 dogs with concurrent medical diseases that could have predisposed to ischemic stroke.…”
Section: Peco Question: Cerebrovascular Diseasesupporting
confidence: 54%
“…Of these dogs, 2 had no underlying disease identified, while the 3 others had PLN, HAC, or hemangiosarcoma identified (LOE 5, Fair) . In another study of 8 dogs with brain infarction identified via CT, 6 of 8 dogs had concurrent diseases including hypothyroidism, chronic renal disease, pyometra, and HAC (LOE 5, Fair) . A third study of 22 dogs included 4 dogs with concurrent medical diseases that could have predisposed to ischemic stroke.…”
Section: Peco Question: Cerebrovascular Diseasesupporting
confidence: 54%
“…Information provided by 3 studies (LOE 5, Fair) suggest that ischemic strokes are more likely the result of a hypercoagulable conditions than a risk factor for thrombosis themselves . None of the dogs included in retrospective studies of PTE, arterial thromboembolism (ATE), portal vein, or splenic vein thrombosis had cerebrovascular disease …”
Section: Guidelinesmentioning
confidence: 99%
“…Three days later, the dog developed acute neurological signs consistent with central dysfunction with right-sided amaurosis, ventromedial strabismus of the left eye, and leftsided Horner's syndrome. 16 Multislice Computed Tomography pre-and postcontrast studies of the brain were performed. A single intraaxial, homogeneous, well-circumscribed, irregularly shaped, hyperattenuating (+/− 62 HU), and noncontrast-enhancing area of 5 mm diameter was observed in the caudal part of the mesencephalon, mildly left-sided, exerting a mild mass effect on the surrounding structures and associated with dilation of the ventricular system ( Figure 1).…”
Section: Case Presentationmentioning
confidence: 99%